Alan Cawson et al.. Hostile Brothers. Competition and Closure in the European Electronics Industry, Oxford: Clarendon Press, 1990, 405 s.; Alberto Martinelli, (ed.), International Markets and Global Firms. A Comparative Study of Organized Business in the - Chr. Sidenius, Niels (Politica, 1992)
Alan Cawson et al.. Hostile Brothers. Competition and Closure in the European Electronics Industry, Oxford: Clarendon Press, 1990, 405 s.; Alberto Martinelli, (ed.), International Markets and Global Firms. A Comparative Study of Organized Business in the Chemical Industry', London: Sage, 1991, 294 s.